Integrating 4E cognition with science and technology studies: a framework for understanding AI applications - Gahrn-Andersen, Rasmus (Frontiers in Artificial Intelligence, 2025)
The paper brings together two different theoretical strands of research, one from cognitive science, the other from Science and Technology Studies. The purpose in so doing is to uncover how cognition interrelates with socio-material practices and AI technology. An integrative framework is presented as a possible way for connecting the two strands while theorizing on their interrelations with AI.